Morocco : Third Review Under the Two-Year Precautionary and Liquidity Line-Staff Report; Press Release; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report, 2014)
This paper reviews Morocco's Third Review Under the Two Year Precautionary and Liquidity Line (PLL). The PLL aims to provide insurance against external risks while supporting the authorities program aimed at reducing fiscal and external vulnerabilities and increasing higher growth. The paper outlines that macroeconomic performance has improved in 2013, but the outlook still hinges on the sustained delivery of reforms. The IMF report highlights that continued improvement in economic conditions depend on the sustained implementation of reforms to further reduce vulnerabilities, strengthen competitiveness, and incur stronger growth.